Peningkatan Pengetahuan dan Pengendalian Penyakit Hipertensi melalui Edukasi Hipertensi pada Masyarakat di Dusun Karangreja - Syahputro, Widodo Dwi; Syamsiah, Resti Ikhda; Engkartini, Engkartini; Kasron, Kasron; Nurrochmah, Fitria Sifa; Fatmawati, Susi; Alkharsi, Muhammad Rahman; Hasanah, Rani Uswatun; Yuliawan, Arif; Yaelaningsih, Salsa Bella; Nisa, Aulia Syahidatun; Monikca, Diah Sely (Pakis Journal Institute, 2025)
Through hypertension education and the manufacture of a bay leaf decoction, this community service project seeks to raise public awareness and reduce hypertension. Twenty samples of hypertensive individuals in Karangreja hamlet, Bantarsari District, Cilacap, were observed analytically. A questionnaire with ten items was used to gather data before and after counseling (pretest and posttest, respectively). Leaflets and the process of creating a decoction from bay leaves were used to educate the public. The average community knowledge before receiving education was 62.5, but after receiving education, the average increased to 86, according to the community service statistics. Nearly every responder reported a rise in comprehension, including those with low starting scores who shown notable improvements. The public's awareness of hypertension can be raised by health counseling on the usage of bay leaf decoction.